Agatha Bârsescu – A World Class Tragedian - POPA, Mircea (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
Following closely the lifetime theatrical vocation of the Romanian actress Agatha Bârsescu, the present article sheds light upon her love for theatre and her international carrier. After spending her childhood in Bucharest and after studying at the Conservatory of Dramatic Art, Agatha was encouraged to try her chance abroad, which she did when, at the age of twenty-two, she passed her admission exam at the Vienna Conservatory School of Drama. Years of brilliant roles and extraordinary meetings followed with an enthusiastic audience in Austria, Germany, and later on, in the United States of America. She was loved, highly appreciated, as an artist and as a teacher, when she came back to Romania, at the Conservatory of Iassy where she instructed young actresses. A model of elegance and professionalism, she left behind a volume of beautiful Memoirs, an important correspondence (at the Vienna Museum of Art) and a large number of precious photographs and articles that critics consecrated to her work and life